The Role of Social Media in Increasing MSME Turnover in Sidenreng Rappang Regency - Zainal, Henni (Pinisi Business Administration Review, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the regional economy, including in Sidenreng Rappang Regency. However, one of the main challenges faced by MSMEs is the limitations in marketing and market reach. Social media has become an effective tool in increasing business visibility and expanding customer networks. This study aims to analyze the role of social media in increasing MSME turnover in Sidenreng Rappang Regency. The research method used is a quantitative approach with a survey technique on MSME actors who actively use social media such as Facebook, Instagram, and WhatsApp as marketing media. Data were collected through questionnaires and interviews, then analyzed using linear regression analysis to see the relationship between social media use and increased business turnover. The results of the study showed that the use of social media has a significant effect on increasing MSME turnover. Factors such as posting frequency, interaction with customers, and the quality of published content have a positive impact on sales. In addition, MSME actors who use digital marketing strategies, such as paid promotions and collaboration with local influencers, tend to experience higher turnover increases compared to those who only rely on conventional methods.